HUBUNGAN TINGKAT KEPARAHAN ACNE VULGARIS DENGAN GAMBARAN DIRI PADA REMAJA KELAS XII - Norma Risnasari; Siti Aizah (Jurnal EDUNursing, 2023)
Acne vulgaris is a chronic inflammation of the pilosebaceous follicles which is a problem for almost all adolescents, where there is an increase an androgen hormones circulating in the blood which can cause hyperplasia and hypertrophy of the sebaceous glands. This problem gives a bad psychological impression on teenagers. Teenage image factors and social interaction activities are very important. Although the problem is considered mild and can be self-treated, if left untreated it will result in bad physical and emotional impressions. The purpose of this study was to analyze the relationship between the severity of acne vulgaris and self-image in Class XII adolescents at Vocational School PGRI 4 Kediri City. The research design used in this study is correlation. Samples were taken from class XII students of Vocational School PGRI 4 Kediri City aged 16-19 who met the inclusion criteria with purposive sampling technique. The sample size is 40 respondents. The instrument used for data collection is a questionnaire. Data processing was performed using the Spearman Nonparametric correlation test with a significant level of p<0.05. The results of data processing using the spearman nonparametric correlation test yielded a relationship between the severity of acne vulgaris and self-image in adolescence with a correlation coefficient of 0.392 with a significant level of 0.0012 (p<0.05). This research is expected that teenagers maintain and care for facial skin regularly to prevent acne so that it can increase self-confidence. Keywords: Severity Level, Acne Vulagris, Adolescents.